2005
DOI: 10.1074/jbc.m507061200
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-induced Conformational Changes in the Membrane-embedded IICmtl-domain of the Mannitol Permease from Escherichia coli, EnzymeIImtl, Probed by Tryptophan Phosphorescence Spectroscopy

Abstract: Membrane-bound transport proteins are expected to proceed via different conformational states during the translocation of a solute across the membrane. Tryptophan phosphorescence spectroscopy is one of the most sensitive methods used for detecting conformational changes in proteins. We employed this technique to study substrate-induced conformational changes in the mannitol permease, EnzymeII mtl , of the phosphoenolpyruvate-dependent phosphotransferase system from Escherichia coli. Ten mutants containing a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Others were the preferred target for uncoupling mutations. Still other residues were found to be critical for exposing substrate molecules bound in the IIC domain to the phosphorylation site in the IIB domain [12,13,15]. These data provide strong evidence that during this process, a conserved area of the EIIC domain with the bound substrate molecule, and the area of the EIIB domain near the phosphorylated cysteine must be, at least temporarily, in close contact.…”
Section: Enzymes II Of the Pts Are Transport Systems And Chemoreceptomentioning
confidence: 79%
See 1 more Smart Citation
“…Others were the preferred target for uncoupling mutations. Still other residues were found to be critical for exposing substrate molecules bound in the IIC domain to the phosphorylation site in the IIB domain [12,13,15]. These data provide strong evidence that during this process, a conserved area of the EIIC domain with the bound substrate molecule, and the area of the EIIB domain near the phosphorylated cysteine must be, at least temporarily, in close contact.…”
Section: Enzymes II Of the Pts Are Transport Systems And Chemoreceptomentioning
confidence: 79%
“…With only few NMR and X-ray crystallography data available for the soluble domains, analysis of the membrane domains relies on indirect data such as sequence alignments, domain complementation, and protein fusion studies [9,10], cysteine crosslinking and accessibility data [12][13][14], tryptophan fluorescence and phosphorescence studies [15], and the analysis of mutants affected in transport, phosphorylation, and in coupling both activities [16][17][18]. According to such data, EIIC(+D) domains from all PTS families comprise at least six typical trans-membrane helices, i.e., α-helices of ≥21 residues length with a hydrophobicity value ≥1.8.…”
Section: Enzymes II Of the Pts Are Transport Systems And Chemoreceptomentioning
confidence: 99%
“…Furthermore, residues in the N-terminal half of MtlA (the region corresponding from TM1 to TM4 in bcCHBC) were shown to be in close contact with mannitol, the sugar was shown to be located closer to the periplasm, and substantial differences were observed between solvent exposed residues in MtlA and their expected counterparts in the bcChbc structure[69, 70]. Tryptophan phosphorescence spectroscopy indicated that F97 in MtlA (a predicted cytoplasmic loop residue that overlays TM3 in bcChbC) is part of a β-sheet fold[71]. Interestingly, this region was shown to undergo large conformational changes upon ligand binding with partial unfolding around F97, indicating that what appears to be essentially a dimerization domain in bcChbC may play a more extensive role in sugar translocation in MtlA[71].…”
Section: Transportmentioning
confidence: 99%
“…are predicted to form a TMH and a periplasmic loop (36) or protrude into the membrane from the cytoplasmic side ( Fig. 2 (29,35,38). These results suggest that residues in this part of IIC mtl are directly involved in the mannitol translocation process.…”
Section: Location Of the Mannitol-binding Site With Respect To Transmmentioning
confidence: 57%
“…Location (29,31) and cysteine accessibility studies (35) show that this part of IIC mtl is highly structured. Indeed, in recent topology models these residues The total intensity was assumed as I(t) ϭ ⌺ i ␣ i exp(Ϫt/ i ) with ⌺ i ␣ i ϭ 1 for the condition with mannitol.…”
Section: Location Of the Mannitol-binding Site With Respect To Transmmentioning
confidence: 99%